Risk scores for choledocholithiasis perform poorly in patients with hemolytic diseases: a PEDI database report - Thompson, Jennifer; Ruan, Wenly; Fishman, Douglas S.; Giefer, Matthew; Kim, Kyung Mo; Martinez, Mercedes; Dall'Oglio, Luigi; Balassone, Valerio; Torroni, Filippo; De Angelis, Paola; Faraci, Simona; Tsai, Cynthia; et al. (Frontiers in Pediatrics, 2025)
Patients with hemolytic diseases are at increased risk for gallstone-related complications. Modified scoring systems have been developed to assess which pediatric patients would benefit from endoscopic retrograde cholangiopancreatography (ERCP) to treat choledocholithiasis. This study aimed to evaluate the ability of the available criteria to determine which pediatric patients with hemolytic diseases are likely to benefit from ERCP. A secondary analysis was performed using the Pediatric ERCP Database Initiative database, which contains prospectively collected data from 1,124 ERCPs at tertiary-care institutions. We compared patients with a hemolytic disease to those without. Data was analyzed by two-tailed Fisher’s exact test and paired student t-test. Of the 47 (17.0%) patients who had a hemolytic disease, 34 (72.3%) had one or more common bile duct (CBD) stones at the time of ERCP. Among patients with hemolytic diseases, there were no differences in pre-ERCP imaging or laboratory findings between those with a CBD stone removed at ERCP and those without. Patients with hemolytic diseases did not fit the current choledocholithiasis selection criteria well: 80% in the no-stone at ERCP group met the American Society of Gastrointestinal Endoscopy high-risk criteria, and 90% met the 2016 modified Baylor pediatric criteria. Although not statistically significant, there was an increased number of adverse events in patients with hemolytic diseases. Existing ERCP criteria perform poorly in patients with hemolytic diseases, overestimating their risk of choledocholithiasis. Peri-procedure evaluations such as endoscopic ultrasound, magnetic resonance cholangiopancreatography, and intraoperative cholangiography appear underutilized and may be essential modalities in this population.